Using time‐weighted average change from baseline of SARS‐CoV‐2 viral load to assess impact of hydroxychloroquine as postexposure prophylaxis and early treatment for COVID‐19. Issue 12 (23rd August 2022) - Kumbhakar, Raaka; Neradilek, Moni; Barnabas, Ruanne V.; Stewart, Jenell; Stankiewicz Karita, Helen C.; Landovitz, Raphael J.; Kissinger, Patricia J.; Jerome, Keith R.; Paasche‐Orlow, Michael K.; Bershteyn, Anna; Chu, Helen Y.; Neuzil, Kathleen M.; et al.
Abstract: Two randomized controlled trials demonstrated no clinical benefit of hydroxychloroquine (HCQ) for either postexposure prophylaxis or early treatment of SARS‐CoV‐2 infection. Using data from these studies, we calculated the time‐weighted average change from baseline SARS‐CoV‐2 viral load and demonstrated that HCQ did not affect viral clearance.